Observation of the marine benthic organisms at Syowa Station in Antarctica using a remotely operated vehicle - Hamada,Etuyuki; Numanami,Hideki; Naito,Yasuhiko; Taniguchi,Akira (1986)
P(論文) The authors participated in the 25th Japanese Antarctic Research Expedition and conducted observation of benthos near Syowa Station in Antarctica using a remotely operated vehicle. In addition to a TV camera, the vehicle was equipped with two still cameras for "stereographic" photographs. As a result of analysis of those photographs, the authors were able to determine the distribution density of benthos. In shallow waters (10 and 16m), motile animals such as urchins (Sterechinus neumayeri) were plentiful, while as the water got deeper (40 and 80m), sessile animals such as tubeworms increased. At the deepest location observed in this study, 200m, Bryozoa were dominant; areas existed where Bryozoa covered the entire seabed. departmental bulletin paper